Дослідження народжуваності й плідності у реальних поколінь жінок України: висновки для сьогодення - Стешенко, В.С. (Інститут демографії та соціальних досліджень НАН України, 2010)
У статті аналізуються показники побудованих автором таблиць народжуваності й плідності для поколінь жінок України 1921/1922–1988/1989 рр. народження з метою розкрити ті особливості дітородної активності жінок, які не можуть бути досліджені методом умовного покоління. Основне завдання даної публікації — зробити висновки з когортного аналізу, які становлять актуальний інтерес для сучасної національної демографічної політики і демографічної статистики. В статье анализируются показатели построенных автором таблиц рождаемости и плодовитости для поколений женщин Украины 1921/1922–1988/1989 гг. рождения с целью раскрыть те особенности детородной активности женщин, которые не могут быть исследованы методом условного поколения. Основная задача данной публикации — сделать выводы из когортного анализа, представляющие актуальный интерес для современной национальной демографической политики и демографической статистики. Indices of the built by the author tables of fertility for Ukrainian women generation of 1921/1922–1988/1989 are analyzed in the article for the purpose to study that peculiarities of childbearing activity which can’t be investigated by the method of conventional generation. The main goal of this publication is to draw a conclusions from cohort analysis which are of interest for contemporary national population policy and demographic statistics (see below).
• Favourable or adverse living conditions at time of birth and early childhood of girl have an effect on her future childbearing behaviour. The study afford ground for the next hypothesis: into «demographic biography» of newborns, into their childbearing potential as future mothers has being inserted optimistic or pessimistic vision of the future which is being formed by that conditions in which have being their mothers during pregnancy and delivery. This phenomenon have an effect during all reproductive period of women, who in childhood has a sensation of one or another peculiar living conditions, that is distinctive steady «psychological memory» exists. Current crisis may carry potential of oppression of future childbearing activity of generation which were born at that period. This hypothesis requires further researches by psychologists.
• Decrease of cohort fertility in crises 1990-is in the age of 20–24, i.e. when women of that cohorts passed through the age-specific fertility maximum shall cause demographic wave in future, which will bring down the effectiveness of population policy in connection with reduction of contingents which are the objects of this policy. Decline of childlessness is evidence of turning birth of firstborns into effectve reserve of demopolitical influence from viewpoint of increase of the births number and from the aspect of auspicious psychological atmosphere formation for decision taking by women concerning next bearing of child.
• The mainstream direction of cohort study expansion have to be cohort researches of mortality and other demographic processes for investigation of interrelations between appropriate indices. In this context the need of improvement of vital and census statistics for cohort studies in compliance with international standards became urgent. In principle new possibilities for cohort study development might open establishment of the state population register.